Funeral Accountability in the Perspective of Islam - Lea Emilia Farida; Sirajudin; Nurul Mukhlisah (Yayasan Rumah Peneleh, 2023)
The purpose of this study is to reveal the accountability of funeral team of the Cilandak sub-district, South Jakarta. As a sub-district that is neither a social organization nor a legal body, the team received funds from The National Zakat Body of DKI Jakarta Province. This study uses a qualitative approach by analyzing in depth the phenomenon of accountability. Data were collected through interviews techniques using an open-ended question model. The funeral care in the Cilandak sub-district implemented four accountability dimensions, as probity and legality, processes, programs, as well as policies. The team also has three accountability principles, namely, responsibility, justice, and truth. Instead of producing financial reports, the team published a unique accountability daily report of Ambulance Arrangement for Covid-19.